2001
DOI: 10.1016/s0022-5347(05)65868-5
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cystectomy Is Safe in Elderly Patients at High Risk

Abstract: Our results support the safety of radical cystectomy in elderly patients at high risk. Acceptable perioperative morbidity and mortality may be achieved without routine intensive monitoring postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(26 citation statements)
references
References 14 publications
2
22
0
2
Order By: Relevance
“…Lack of association may be secondary to relative lack of sensitivity of ASA and limited sample size. Chang et al [24] also used ASA scores and had relatively small samples sizes, which may have contributed to their negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of association may be secondary to relative lack of sensitivity of ASA and limited sample size. Chang et al [24] also used ASA scores and had relatively small samples sizes, which may have contributed to their negative results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RC demonstrates a 3-5-fold higher perioperative mortality in septuagenarians (5.4%) and octogenarians (9.2%) in comparison to patients ≤ 69 years (2%) (5). Some studies, however, have demonstrated that selected older patients have similar peri-operative outcomes as younger patients (6)(7)(8). Bladder sparing treatment in a selected group of octogenarians has also been successfully demonstrated by Wehrberger et al (9).…”
Section: Introductionmentioning
confidence: 93%
“…Most studies evaluating complications after RC have not used standardized reporting criteria, applied different definition of complications and the length of follow-up after surgery differed significantly [7]. However, regardless of the definition used, studies from high volume centers have reported lower complication rates varying between 0.9-11% [17,18], suggesting that this type of surgery yields better results when performed by high volume surgeons in specialized tertiary care units. Postoperative care is paramount in these cases, since most of the complications are mainly medical, such as bronchopneumonia, deep vein thrombosis/pulmonary thromboembolism, delirium and myocardial infarction [7].…”
Section: Complications After Surgical Treatmentmentioning
confidence: 99%